The Influence of Ziska (The Wheel of Karma) on the Novel Phitsawat - Puyatorn, Kannapohn (Journal of Cultural Analysis and Social Change, 2026)
This study examines the influence of the novel Ziska (Kongkwian) on the Thai novel Phitsawat. The main objectives are to analyze how Ziska influences Phitsawat and to explore the distinctive characteristics of both novels. The findings show that Phitsawat is indeed influenced by Ziska. A comparative analysis of plot, characters, setting and atmosphere, narrative techniques, and thematic ideas reveals several important similarities between the two works.Both novels feature female characters Sarochinee and Princess Ziskawho appear in ancient-style clothing, creating a sense of mystery connected to the past. In addition, the palace or house associated with these characters is portrayed as mysterious and unsettling in both stories. Another shared element is the presence of strange and frightening paintings that contrast sharply with reality. Furthermore, sacred or supernatural beings play an important role as witnesses to the final moments of the characters, reinforcing the spiritual dimension of both narratives.A distinctive feature of Ziska is its integration of social criticism, along with its emphasis on the consequences of karma. Although Phitsawat is clearly influenced by Ziska, it also has its own unique characteristics. Phitsawat strongly reflects Thai cultural identity, particularly through the concept that hatred should be ended through forgiveness rather than revenge. In addition, the use of a homophonic title adds a special literary dimension to the novel. These features demonstrate the creativity of Thamayanti in adapting foreign literary influence into a narrative that is harmonious with and meaningful within the context of Thai society.